Peningkatan Pengelolaan Keuangan Pada Kelompok Usaha Jajanan Khas Ndeso di Kelurahan Salamsari Kecamatan Boja Kabupaten Kendal - Teti Susilowati; Muryanto Agus Nuswantoro; Emy Susiatin (Lembaga Pengembangan Kinerja Dosen, 2024)
Salamsari Village is a village located in the southern part of Boja District, Kendal Regency. This village is located in the highlands of Kendal Regency where the majority of Salamsari village residents work as agricultural laborers and traders. Most of the food processing businesses are housewives. Several business actors who named their group joined the name Jajanan Khas Ndeso which sells several processed snacks including: various criping (criping cassava, banana, taro, breadfruit, etc.), various peyek (peyek nuts, anchovies, dele, etc.), kembang goyang, cendol savory, widaran, tempe chips, lumpit, and others. The aim of this activity is to improve financial management in the Ndeso Typical Snacks business group in Salamsari Village, Boja District, Kendal Regency. In running their business, they have not managed it well, meaning that in terms of administration, there has been no proper and correct recording. For some business actors, there are even bookkeeping or financial management that is still mixed up with their household finances, so they cannot know for sure how much profit they have earned from the business, as well as difficulties in knowing the development of the business they are running. Based on this, the service team has an interest to carry out outreach related to financial management, including about bookkeeping which must be separate from household finances, as well as simple reporting with related businesses. So that you can know the profits and financial position so that you can determine the direction of business development better and increase. We will publish the output targets from this trial in national journals, HKI, YouTube and through mass media.